1997
DOI: 10.1139/t97-030
|View full text |Cite
|
Sign up to set email alerts
|

Seventeenth Canadian Geotechnical Colloquium: The effect of cohesion loss and stress path on brittle rock strength

Abstract: Stress-strain curves for brittle rocks show three characteristic stress levels: crack initiation, long-term strength, and peak strength. Damage-controlled testing at low confining stresses has shown that the long-term and peak strengths are sensitive to the amount of induced damage, i.e., the greater the amount of damage, the lower the long-term and peak strengths. These tests also showed that the brittle-failure process is characterized by a loss of cohesion as friction is mobilized. Excavation of a circular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
177
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 554 publications
(234 citation statements)
references
References 26 publications
11
177
0
5
Order By: Relevance
“…The comparisons between our methods and theirs are listed here to show the difference between these thresholds. Martin (1993) suggested one to use calculated crack volumetric strain to identify crack initiation. For a uniaxially loaded sample, crack volume is determined by subtracting the linear elastic component of the volumetric strain, given by:…”
Section: Relationship Between Stress Strain and Ae Countsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparisons between our methods and theirs are listed here to show the difference between these thresholds. Martin (1993) suggested one to use calculated crack volumetric strain to identify crack initiation. For a uniaxially loaded sample, crack volume is determined by subtracting the linear elastic component of the volumetric strain, given by:…”
Section: Relationship Between Stress Strain and Ae Countsmentioning
confidence: 99%
“…Martin (1993) defines crack initiation as the stress level at which dilation (i.e., crack volume increase) begins in the crack volume plot. Taking the typical cylindrical specimen A3 and rectangular prism specimen C3 as examples, the stress-strain curves, the AE count rate curve and the stress thresholds are plotted in Figs.…”
Section: Relationship Between Stress Strain and Ae Countsmentioning
confidence: 99%
“…In addition it is shown that the monotonic results act almost as a failure locus in the q − ǫ 1 plane for the cyclic results at identical confinement. A conclusion of the study presented by Martin & Chandler (1994); Martin (1997) is that cohesion is progressively decreased cycle after cycle as a consequence of sample damaging. This is correlated with the opening and propagation of microcracks.…”
Section: Experimental Reviewmentioning
confidence: 99%
“…Lac du Bonnet granite is a well studied rock material (Martin & Chandler, 1994;Chow et al, 1995;Martin, 1997;Eberhardt et al, 1999a,b), exhibiting clearly a brittle behaviour as shown in Fig20. Elastic and failure parameters are calibrated with respect to literature.…”
Section: Lac Du Bonnet Granitementioning
confidence: 99%
“…Breakout around a large-scale underground excavation was studied in detail at the AECL Mine-by experimental tunnel (Read, 1994;Martin and Read, 1996;Martin, 1997). Hajiabdolmajid, Kaiser, and Martin (2002) successfully simulated damage around the Mine-by tunnel using a cohesion-weakening and frictional-strengthening strainsoftening (CWFS) model implemented in the FLAC program ( Figure 19).…”
mentioning
confidence: 99%